Pengaruh Human Capital dan Technological Capital terhadap Kinerja Lembaga Amil Zakat - Agil Darmawan; Dedy Rachmad; Rininta Nurrachmi (Department Islamic Economics, 2023)
This study aims to analyze the influence of human capital and technological capital on the performance of Zakat Institutions (LAZ) in Indonesia using the Intellectual capital theory. The method used in this research is Partial Least Square-Structural Equational Modeling (PLS-SEM) and processed using SmartPLS 3.2.9. A total of 129 amils and 105 LAZs were contributed as research respondents. Data were obtained primarily by distributing questionnaires via google form with a likert scale of 1-5. From the research results, it was found that the two independent variables, both human capital and technological capital, have a significant and positive influence on the performance of zakat institutions. With a determination coefficient value of 51.1%, so that in further research, other variables need to be involved.